Philip Taaffe: The Life of Forms- Works 1980-2008 - Taaffe, Philip (Hatje Cantz Verlag, 2008)
Exhibition catalog. Mar-Jun 2008 @Kunstmuseum Wolfsburg. New York-based painter Philip Taaffe became internationally known as part of the early-80s Appropriation art movement for his unique approach, which combined abstraction with ornamental art from a variety of cultures. Poet and critic John Yau has written, "In attempting to connect the microcosmic with the macrocosmic, Taaffe constructs a metaphysical vertical axis that connects earth to sky, as well as the ancient to the postmodern." Taaffe has traveled extensively, building a lexicon of imagery from cultures with a history of ornate decorative art, among them Arabic, Asian, Celtic and Pre-Colombian. Within the confines of his canvases, imagery from these civilizations mingles freely together, and merges with influences from the Western canon, such as Art Nouveau, Op art and Abstract Expressionism. Taaffe also uses non-art sources like early botanical photography. This substantial new monograph provides an overview of Taaffe's entire oeuvre, with all works beautifully reproduced on full-page color plates. The volume also includes a visual essay by Taaffe and a series of photographs showing him at work in his studio.
English
Keywords: ND49-813 History; USA